(3EOGQI GdJecjf h GbJUGOjGJ GdKbI aj efXeGJ CYeGd GdCdajI GdKGdKIs - (3RcQjG eWdc(B, (3GdOhQjs; (3CMeO Ydj UGdM(B, s ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2009)
(3jVe Jecjf GdYGedjf efgL eJcGed aj EWGQ GSJQGJjLjI EOGQI GdLhOI GdTGedI, GSJQGJjLjI Jecjf GdYGedjf hCKQgG aj JMbjb GdejRI GdJfGaSjI, GdEfaGb Ydi QCS GdeGd GdacQj hCKQg aj fLGM GdTQcGJ GdUfGYjI, efgLjI GdHMK, YQV hJMdjd fJGFL GdHMK GdejOGfj, JMdjd eYWjGJ GdYdGbI GdEQJHGWjI Hjf fXGe eYdheGJ GdehGQO GdehGQO GdHTQjI hQCS GdeGd GdacQj, GdEWGQ GdJMdjdj ddHMK hUa GdeJZjQGJ GdCSGSjI hJMdjd GdYdGbGJ GdEQJHGWjI, GbJUGOjGJ GdKbI CMO eQJcRGJ QCS GdeGd GdELJeGYj GdJfXjej, OhQ GdMGcejI aj JYRjR GdKbI Hjf CUMGH GdeUGdM aj efXeGJ GdCYeGds
(3HjHdjhZQGajG(B: (3U U(B.411-415s
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdCaQGOs; (3VHW GdLhOIs